A Case with Significant Proteinuria Caused by Secreted Protein from Urothelial Carcinoma - Masanori Sakakima; Yoshihide Fujigaki; Hideo Yasuda; Akashi Togawa; Tomoyuki Fujikura; Atsushi Otsuka; Seiichiro Ozono; Akira Hishida (Case Reports in Nephrology)
58-year-old female was admitted to our hospital complaining isolated proteinuria of 1.7 g/day. Abdominal echography showed right-sided unilateral hydronephrosis, and computed tomography pointed out a tumor of the right renal pelvis, suggesting cancer of renal pelvis. The right nephroureterectomy was carried out. Pathological diagnosis was urothelial carcinoma. Renal tissue revealed no apparent glomerulopathy with tubular atrophy, interstitial fibrosis, and mildly-to-moderately interstitial mononuclear cell infiltration. Immunofluorescence study showed no deposition of immunoreactanct, and electron microscopy showed almost normal glomerulus without electron dense deposit. Proteinuria disappeared within 6 days after the operation. Moderate amount of proteinuria in our patient was probably caused by secreted protein from urothelial carcinoma. This condition is rare but should be taken into account in patients with even moderate amount of proteinuria.